2011
DOI: 10.1038/ng.884
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in NBEAL2, encoding a BEACH protein, cause gray platelet syndrome

Abstract: Next-generation RNA sequence analysis of platelets from an individual with autosomal recessive gray platelet syndrome (GPS, MIM139090) detected abnormal transcript reads, including intron retention, mapping to NBEAL2 (encoding neurobeachin-like 2). Genomic DNA sequencing confirmed mutations in NBEAL2 as the genetic cause of GPS. NBEAL2 encodes a protein containing a BEACH domain that is predicted to be involved in vesicular trafficking and may be critical for the development of platelet α-granules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
183
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(186 citation statements)
references
References 14 publications
3
183
0
Order By: Relevance
“…Although the first description of a patient with GPS was reported in 1971 (32), it took until 2011 for NBEAL2 to be identified as the mutated gene causing the disease, a finding which thereby provided the molecular basis for detailed studies on the function and (patho-)physiological significance of α-granules, the most abundant organelles in platelets (19)(20)(21). Our study now provides compelling complementary evidence that NBEAL2 is essential for platelet α-granule biogenesis and establishes the Nbeal2 -/-mouse as a valuable animal model of GPS that recapitulates many of the symptoms found in patients with GPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the first description of a patient with GPS was reported in 1971 (32), it took until 2011 for NBEAL2 to be identified as the mutated gene causing the disease, a finding which thereby provided the molecular basis for detailed studies on the function and (patho-)physiological significance of α-granules, the most abundant organelles in platelets (19)(20)(21). Our study now provides compelling complementary evidence that NBEAL2 is essential for platelet α-granule biogenesis and establishes the Nbeal2 -/-mouse as a valuable animal model of GPS that recapitulates many of the symptoms found in patients with GPS.…”
Section: Discussionmentioning
confidence: 99%
“…Only recently, different mutations in the neurobeachin-like 2 (NBEAL2) gene have been identified in patients with GPS (19)(20)(21). NBEAL2 is a 302-kDa large member of the BEACH-WD40 domain protein family.…”
Section: Introductionmentioning
confidence: 99%
“…This was nicely illustrated in a recent study showing how GPS platelets are unable to deposit a-granule matrix proteins such as fibrinogen (Fg) and fibronectin or provide a a-granule-derived membrane pool for optimal platelet spreading and for consolidating platelet connections on microlesions of exposed subendothelium [9]. Notwithstanding the phenotypic variability, a large number of GPS families, all with autosomal recessive inheritance, genotyped with biallelic mutations in NBEAL2 [10][11][12][13]. Significantly, neurobeachin-like 2 (NBEAL2) is predicted to be scaffolding protein that intervenes in vesicle trafficking, it contains a Beige and ChediakHigashi (BEACH) domain also seen in lysosomal trafficking regulator (LYST) mutated in the Chediak-Higashi syndrome and associated with abnormal lysosomes and dense granules [14].…”
Section: Gray Platelet Syndrome and The Nbeal2 Genementioning
confidence: 98%
“…Quite recently, Rensing-Ehl et al [18] have reported that GPS can phenotypically mimic autoimmune lymphoproliferative syndrome (ALPS). Members of two families diagnosed with ALPS combined thrombocytopenia (or pancytopenia), enlarged "gray" platelets on blood smear, a much reduced platelet P-selectin expression after platelet activation with high plasma levels of vitamin B 12 and soluble Fas ligand (sFASL) often considered as a marker of inflammation and apoptosis. Yet, FAS mutations frequently seen in ALPS, were absent.…”
Section: Gray Platelet Syndrome and The Nbeal2 Genementioning
confidence: 99%
“…Nonetheless, Kahr's group and others have recently demonstrated that mutations in NBEAL2, which encodes neurobeachin-like protein 2, cause GPS. [3][4][5] Even before this work, however, Kahr and colleagues had characterized another syndrome associated with ␣-granule deficiency termed arthrogryposis, renal dysfunction, and cholestasis (ARC) syndrome. 6 ARC syndrome is a rare autosomal recessive condition characterized by death in the first year of life.…”
Section: ␣-Granules: a Story In The Making --------------------------mentioning
confidence: 99%